Analytical Method Development and Validation of Brivaracetam in API and Marketed Formulation by RP-HPLC - Bhadru, Banothu; Naveen Kumar, Peddinti; Sujatha, Damera; Renukuntla, Pranay; Boggula, Narender (Asian Journal of Pharmaceutical Research and Development, 2024)
A rapid and precise reverse phase high performance liquid chromatographic method has been developed for the validated of brivaracetam in its pure form as well as in tablet dosage form. Chromatography was carried out on a Symmetry ODS RP C18,5mm, 15mm x 4.6mm column using a mixture of phosphate buffer: methanol: acetonitrile (30:35:35% v/v) as the mobile phase at a flow rate of 1.0ml/min, the detection was carried out at 285 nm. The retention time of the brivaracetam was 2.183. The method produces linear responses in the concentration range of 60-140μg/ml of brivaracetam. The method precision for the determination of assay was below 2.0%RSD. The method was found to be sensitive, accurate and precise useful in the quality control of bulk and pharmaceutical formulations.